2022
DOI: 10.1021/acsnano.1c09636
|View full text |Cite
|
Sign up to set email alerts
|

Large Area Ultrathin InN and Tin Doped InN Nanosheets Featuring 2D Electron Gases

Abstract: Indium nitride (InN) has been of significant interest for creating and studying two-dimensional electron gases (2DEG). Herein we demonstrate the formation of 2DEGs in ultrathin doped and undoped 2D InN nanosheets featuring high carrier mobilities at room temperature. The synthesis is carried out via a two-step liquid metal-based printing method followed by a microwave plasma-enhanced nitridation reaction. Ultrathin InN nanosheets with a thickness of ∼2 ± 0.2 nm were isolated over large areas with lateral dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…10,11 This high operating temperature of MOS-based gas sensors is faced with the challenges of safety and energy consumption that makes it difficult to apply in the emerging technologies of 5G and Internet of Things (IoT). 12,13 Two-dimensional (2D) materials, which are defined as a few atomic layers, are often considered to be a potential candidate for future-generation photonics, 14,15 electronics, 16 supercapacitors, 17 and catalysts 18 due to their distinctive morphological, electronic, physiochemical, and optical properties. 19−22 Thanks to the merits of large surface areas and numerous active sites, 2D materials including, but not limited to, graphene, 23 boron nitride, 24 violet phosphorus, 25 and MXene 26 have been increasing interest in the application of gas sensing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 This high operating temperature of MOS-based gas sensors is faced with the challenges of safety and energy consumption that makes it difficult to apply in the emerging technologies of 5G and Internet of Things (IoT). 12,13 Two-dimensional (2D) materials, which are defined as a few atomic layers, are often considered to be a potential candidate for future-generation photonics, 14,15 electronics, 16 supercapacitors, 17 and catalysts 18 due to their distinctive morphological, electronic, physiochemical, and optical properties. 19−22 Thanks to the merits of large surface areas and numerous active sites, 2D materials including, but not limited to, graphene, 23 boron nitride, 24 violet phosphorus, 25 and MXene 26 have been increasing interest in the application of gas sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) materials, which are defined as a few atomic layers, are often considered to be a potential candidate for future-generation photonics, , electronics, supercapacitors, and catalysts due to their distinctive morphological, electronic, physiochemical, and optical properties. Thanks to the merits of large surface areas and numerous active sites, 2D materials including, but not limited to, graphene, boron nitride, violet phosphorus, and MXene have been increasing interest in the application of gas sensing. For example, the violet phosphor with a thickness of 2.16 nm is capable of rapid detection of 50 ppm of dimethylamine gas at room temperature .…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that 2D materials can be fabricated via the method of 'liquid metal chemistry' (LMC) [28], which promises the integration of 2D materials onto photonic devices with more ease than traditional methods. This method is a two-step process consisting of a liquid metal-based printing method followed by a microwave plasma-enhanced nitridation reaction [29]. The term liquid metals covers metals and metal alloys present in liquid form below approximately 350°C, which includes several post-transition elements, group 12 elements, and their alloys [30].…”
Section: Introductionmentioning
confidence: 99%
“…These properties make gallium-based alloys particularly suitable for a wide range of applications in flexible electronics and soft robotics alongside chemical and electrochemical processes. In the context of electrochemistry, one of the most intriguing merits of liquid metals is the dynamic liquid–liquid interface that is established when they are in contact with an immiscible electrolyte . The liquid metal–electrolyte interface offers an atomically smooth yet electrochemically active template for growing or depositing a range of precursors into thin layers, , which presents great tunability for synthesizing materials in the nanoscale. , …”
Section: Introductionmentioning
confidence: 99%
“…13−15 In the context of electrochemistry, one of the most intriguing merits of liquid metals is the dynamic liquid−liquid interface that is established when they are in contact with an immiscible electrolyte. 16 The liquid metal−electrolyte interface offers an atomically smooth yet electrochemically active template for growing or depositing a range of precursors into thin layers, 17,18 which presents great tunability for synthesizing materials in the nanoscale. 19,20 The liquid metal−electrolyte interface normally provides a highly reducing autogenous surface potential, which is able to reduce a wide range of oxidizing ionic precursors by selecting a suitable electrolyte.…”
Section: Introductionmentioning
confidence: 99%